2022
DOI: 10.3390/antiox11020433
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds, Vitamins C and E and Antioxidant Activity of Edible Honeysuckle Berries (Lonicera caerulea L. var. kamtschatica Pojark) in Relation to Their Origin

Abstract: Honeysuckles are frost tolerant plants providing early-ripening fruits with health-promoting properties which have been used in traditional medicine in China. This study evaluates the impact of the climatic conditions of two areas on the chemical composition and antioxidant activity (AOA; by DPPH—2,2-diphenyl-1-picrylhydrazyl and photochemiluminescence assays) of eight cultivars of honeysuckle berries (Lonicera caerulea L. var. kamtschatica Pojark) of various ripening times. Expectedly, chemical composition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…As noted previously, antioxidants react with DPPH • stable radicals via a combined hydrogen atom transfer (HAT) and single electron transfer mechanism (SET). This fact also indicates the advantage of using the DPPH • molecule in the study of the antioxidant/antiradical properties of substances [ 2 , 3 , 4 , 5 , 6 ]. The use of the molecule as a model in the reaction with AO makes it possible to measure the integral capacity, which simultaneously includes two mechanisms of antioxidant action in the body.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted previously, antioxidants react with DPPH • stable radicals via a combined hydrogen atom transfer (HAT) and single electron transfer mechanism (SET). This fact also indicates the advantage of using the DPPH • molecule in the study of the antioxidant/antiradical properties of substances [ 2 , 3 , 4 , 5 , 6 ]. The use of the molecule as a model in the reaction with AO makes it possible to measure the integral capacity, which simultaneously includes two mechanisms of antioxidant action in the body.…”
Section: Resultsmentioning
confidence: 99%
“…It has a deep purple color, which is widely used in the spectrophotometry. The DPPH • , interacting with antioxidants, transforms into a reduced diamagnetic form with a pale-yellow color [ 2 , 3 ]. The rate of decrease of the optical density at the maximum absorption of the radical can be used to evaluate the antioxidant/antiradical properties of individual compounds, added to the solution, and their complex mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants are among the most effective natural defenses against disease, offering protection against stressors that might otherwise harm cellular structures. Numerous fruits, vegetables and other plant materials are natural sources of compounds with protective activities, including antioxidant, anticancer, antibacterial, antiviral, antiseptic, anti-inflammatory and anti-allergic compounds [ 70 , 71 , 72 , 73 , 74 ]. Furthermore, the desire to increase fruit and vegetable consumption in the human diet is partially due to the favorable effects of beneficial antioxidants found in these foods on health promotion.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C is another component with important health benefits, with concentrations of 85–300 mg/kg, and even up to 1860 mg/kg FW according to some authors, which are among the highest found in known fruits [ 28 , 81 ]. Additionally, vitamin E in haskap fruits may range between 0.90–3.70 mg/kg DW [ 82 ].…”
Section: Bioactive Compounds Of Lonicera Caerulea ...mentioning
confidence: 99%
“…A. melanocarpa [ 162 , 163 , 164 , 165 ] and L. caerulea [ 24 , 82 , 121 , 166 ] are among the medicinal plants for which the literature reports multiple beneficial effects. Therefore, many bioactive compounds are extracted from these plants and are encapsulated into controlled release systems [ 167 , 168 , 169 , 170 , 171 , 172 , 173 ].…”
Section: Encapsulation and Delivery Systems Of The Bioactive Compoundsmentioning
confidence: 99%